2007
DOI: 10.1121/1.2737668
|View full text |Cite
|
Sign up to set email alerts
|

Otoacoustic emission sensitivity to low levels of noise-induced hearing loss

Abstract: With the aim of investigating the capability of otoacoustic emission (OAE) in the detection of low levels of noise-induced hearing loss, audiometric and otoacoustic data of young workers (age: 18-35) exposed to different levels of industrial noise have been recorded. These subjects are participating in a long-term longitudinal study, in which audiometric, exposure (both professional and extra-professional), and OAE data (transient evoked and distortion product) will be collected for a period of several years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 38 publications
(32 reference statements)
2
23
0
2
Order By: Relevance
“…As it had already been demonstrated in previous studies (Lucertini et al, 2002;Sisto et al, 2007), OAE-based tests are able to discriminate at a statistically significant level the exposed groups from the control group in the case of noise exposure. In this work it is also demonstrated that the measured levels of exposure to styrene are sufficient to significantly affect the OAE response level.…”
Section: Discussionmentioning
confidence: 56%
“…As it had already been demonstrated in previous studies (Lucertini et al, 2002;Sisto et al, 2007), OAE-based tests are able to discriminate at a statistically significant level the exposed groups from the control group in the case of noise exposure. In this work it is also demonstrated that the measured levels of exposure to styrene are sufficient to significantly affect the OAE response level.…”
Section: Discussionmentioning
confidence: 56%
“…In the longitudinal study by Shupak et al, 2007, abnormal TEOAE parameters after the fi rst year of noise exposure had high sensitivity (86 -88%) for the prediction of noise-induced hearing loss after two years. Sisto et al, 2007 in a study of 217 young workers exposed to industrial noise showed that if both OAE data and audiometric data are averaged over a suf fi ciently large bandwidth, the correlation between DPOAE levels and audiometric hearing threshold is suffi cient to design OAEbased diagnostic tests with good sensitivity and specifi city. Hence, further research into the OAE testing is required to improve sensitivities and specifi cities to enable its use as a modality of hearing screening, but its realm of use may perhaps be as a predictor for future noise induced hearing loss rather than a test on its own right.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, high correlation has been found in several cross-sectional studies between audiometric threshold levels and OAE levels (e.g. Lucertini et al, 2002;Sisto et al, 2007). OAEs provide therefore objective diagnostics of the performances of the peripheral auditory receptor, at least in cross-sectional studies, without having necessarily to rely also on direct audiometric threshold measurements.…”
Section: Introductionmentioning
confidence: 96%